PEMANFAATAN LIMBAH ORGANIK RUMAH TANGGA MENJADI CAIRAN MULTIGUNA ECO ENZYME: Utilization of Household Organic Waste Becomes Cairan Multiguna Eco Enzyme - Wantania, Johanna Zusye; Roring, Verawati Ida Yani; Rahardiyan, Dino; Moko, Emma Mauren; Rawung, Livana Dethris (Vivabio: Jurnal Pengabdian Multidisiplin, 2025)
Household waste contributes the largest share of daily waste production, necessitating waste management and the participation of women, as those responsible for managing household waste. Eco Enzyme is a product processed from organic waste to produce a multi-purpose liquid that is highly beneficial for women as housewives. The purpose of this activity is to manage waste through the production of eco-enzyme for women in the Sion Ranomut Congregation. This activity increases the knowledge and skills of women in waste management. Furthermore, this activity serves as a means of dissemination and training for women, fostering their enthusiasm and love for the environment at home and beyond. It also serves as a platform for lecturers to implement knowledge and conduct off-campus activities to achieve the Key Performance Indicators for Universities and Campuses with Impact. ABSTRAK Sampah rumah tangga menyumbang jumlah terbesar terhadap produksi sampah sehari-hari sehingga perlu tindakan pengolahan sampah dan partisipasi dari Wanita Kaum Ibu yang merupakan salah satu yang bertanggung jawab untuk mengelola sampah hasil kegiatan rumah tangga. Eco Enzyme merupakan salah satu produk olahan dari limbah organik untuk menghasilkan cairan serbaguna yang sangat bermanfaat untuk kebutuhan wanita kaum ibu sebagai ibu rumah tangga. Tujuan kegiatan ini adalah pengelolaan sampah dengan pembuatan melalui pembuatan Eco Enzyme bagi wanita kaum ibu di Jemaat Sion Ranomut. Melalui kegiatan ini terjadi peningkatan pengetahuan dan ketrampilan wanita kaum ibu tentang pengelolaan sampah, selain itu kegiatan ini menjadi media diseminasi dan pelatihan bagi wanita kaum ibu dalam menumbuhkan semangat dan kecintaan wanita kaum ibu terhadap lingkungan di rumah dan sekitarnya serta bagi dosen dalam implementasi ilmu pengetahuan serta melakukan kegiatan luar kampus dalam upaya pencapaian Indikator Kinerja Utama Perguruan Tinggi dan Kampus berdampak.